Temperature scaling of ferroelectric hysteresis in hard lead zirconate titanate bulk ceramic - Yimnirun R. (2014)
The temperature scaling of the ferroelectric hysteresis was investigated in hard lead zirconate titanate (PZT) bulk ceramic. The power-law temperature scaling relations were obtained for hystersis area »A «, remnant polarization Pr, and coercivity EC in the forms of » A « T-0.9650, Pr α T-0.0261, and EC α T-0.8823, respectively, which are mostly comparable to those of its soft counterpart. The observation that Pr decayed more slowly with temperature than in soft PZT was attributed to the presence of the complex defects in hard PZT. However, the product of P r and EC still provided the similar scaling law on the T dependence in comparison with » A «. © 2007 Springer-Verlag.